Immunological memory in a teleost fish: common carp IgM+ B cells differentiate into memory and plasma cells - Chan, Justin Tze Ho; Picard-Sánchez, Amparo; Dedić, Neira; Majstorović, Jovana; Rebl, Alexander; Holzer, Astrid Sibylle; Korytář, Tomáš (Frontiers in Immunology, 2024)
From ancient cold-blooded fishes to mammals, all vertebrates are protected by adaptive immunity, and retain immunological memory. Although immunologists can demonstrate these phenomena in all fish, the responding cells remain elusive, without the tools to study them nor markers to define them. Fundamentally, we posited that it is longevity that defines a memory cell, like how it is antibody production that defines a plasma cell. We infected the common carp with Sphaerospora molnari, a cnidarian parasite which causes seasonal outbreaks to which no vaccine is available. B cells proliferated and expressed gene signatures of differentiation. Despite a half-year gap between EdU labeling and sampling, IgM+ B cells retained the thymidine analogue, suggesting that these are at least six-month-old resting memory cells stemming from proliferating precursors. Additionally, we identified a lymphoid organ-resident population of plasma cells by the exceptional levels of IgM they express. Thus, we demonstrate that a teleost fish produces the lymphocytes key to vaccination success and long-term disease protection, supporting the idea that immunological memory is observable and universal across vertebrates.